PERAN AMTHA - Abdul Syukkur (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2018)
Al-Quran is the words of Allah that becomes guidances for human being. Every human has been equipped with intellect as an instrument for receiving these guidances. In delivering His messages in al-Quran, Allah sometimes uses amtha>l to wake up the soul and to make easy to understand and contemplate the messages, so human is able to reach its contents, to carry out Hiscommands and stay away from His prohibitionseasily. This writing will analyze the role of amtha>l, that is not just as instrument of themiracles of al-Quran, but also a tool for wakening human soul. By using amtha>l, human soul as reader can easily accept the messages. Amtha>l of al-Quran is a method in elaborating its contents form the aesthetic point of view. Besides that, amtha>lalso makes easier in understanding verses on metaphisical and phisical things.